THE IMPACTS OF LAND USE AND CONSERVATİON DECİSİONS ON LAND MARKETS İN ENVİRONMENTAL CONSERVATİON AREAS OF TURKEY: A CASE OF GÖKOVA SPECİAL ENVİRONMENT PROTECTİON AREA (Third Sector Social Economic Review, 2011)
Technological developments and economy politics are rapidly destroying non-renewable natural resources and particularly leading to the depletion of non-renewable resources. Within this perspective, attempts to protect the environmental resources were first initiated at the end of the 18th century and emerged from a national scale to a global one starting from the second half of the 20th century. Field-based conservation approaches in the protection of natural and cultural environmental values have gained significance in the 20th century. There are numerous conservation areas in Turkey with such varying legal statutes as historic conservation areas, national parks, special environmental protection areas, natural parks, and nature conservation areas. However, determination of conservation areas at a land plot level, registration and identification procedures, planning for protection, establishment of a rational conservation-utilization balance, and development of well functioning management models directly impact the efficiency of the policies. In the environmental protection areas, and more specifically in Gökova and other special environmental protection zones, economic and financial instruments that could remedy the income and land value losses of owners brought about by the limitations imposed upon land use have not been established. In the settlement areas within the boundaries of the studied region, it has been identified that the annual average number of purchase-sale of land, land rental rates and estimated market values of the lands remain relatively lower as compared to similar settlement areas outside the borders of the examined area. It should be stressed that the communities living inside and in the vicinity of the study area not allowed to participate in the management of environmental conservation areas and that the limitations enforced upon settlement, agriculture, tourism, and other uses within the region in line with the objectives of the area administration (public) can lead to losses in household income and real estate values; however, the current legal and institutional arrangements are unable to remedy the welfare losses of owners.
Keywords: Environmental Conservation Areas; Land Use; Land Market and Land Management